Pengaruh Cash Flow, Kepemilikan Manajerial dan Growth Opportunity Terhadap Konservatisme Akuntansi - Setyaningrum, Wulan; Meta Nursita (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2024)
This research aims to empirically prove the influence of cash flow, managerial ownership and growth opportunity on accounting conservatism. This research was conducted by taking a sample of financial sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2023. The type of data used in this research is secondary data in the form of financial reports that have been audited and published on the Indonesia Stock Exchange (BEI) from 2018-2023. The samples were collected using a purposive sampling method with the number of companies sampled being 11 companies with a research period of 6 years, thus obtaining 66 data. The results of this research show that: (1) Cash Flow, Managerial Ownership and Growth Opportunity have an effect on Accounting Conservatism, (2) Cash Flow has an effect on Accounting Conservatism, (3) Managerial Ownership has an effect on Accounting Conservatism, (4) Growth Opportunity has an effect on Conservatism Accountancy.